Moderators of ayahuasca’s biological antidepressant action - Sousa, Geovan Menezes de; de Oliveira Tavares, Vagner Deuel; de Menezes Galvão, Ana Cecília; de Almeida, Raíssa Nóbrega; Palhano-Fontes, Fernanda; Lobão-Soares, Bruno; de Morais Freire, Fúlvio Aurélio; Nunes, Emerson Arcoverde; Maia-de-Oliveira, João Paulo; Perkins, Daniel; Sarris, Jerome; de Araujo, Dráulio Barros; et al. (Frontiers in Psychiatry, 2022)
The understanding of biological responses to psychedelics with antidepressant potential is imperative. Here we report how a set of acute parameters, namely emotional (depressive symptoms), cognitive (psychedelic experience) and physiological (salivary cortisol), recorded during an ayahuasca dosing session, modulated serum brain-derived neurotrophic factor (BDNF), serum cortisol (SC), serum interleukin 6 (IL-6), plasma C-reactive protein (CRP) and salivary cortisol awakening response (CAR) analyzed two days after the intervention in treatment-resistant depressive patients and healthy volunteers, comparing with a placebo substance. These measures were conducted in a randomized double-blinded, placebo-controlled trial (n=72). We observed that larger reductions of depressive symptoms during the dosing session significantly moderated higher levels of SC in patients. Whereas lower changes in salivary cortisol levels during ayahuasca experience were related to higher BDNF levels in patients with larger clinical response, which means reduction in depressive symptoms. No moderator was found for patient’s CAR, IL-6, and CRP responses to ayahuasca and for all biomarkers responses to ayahuasca of healthy controls, as well as all biomarkers’ responses to placebo substance. In summary, some specific emotional and physiological parameters during experimental ayahuasca session were revealed as critical moderators of the improvement of major depression biomarkers, mainly BDNF and SC two days after entheogen intake. These findings contribute to paving the way for future studies investigating the biological antidepressant response to psychedelic therapy.